Coral reefs and the slow emergence of institutional structures for a glocal land- and sea-based collective dilemma. (February 2020) - Schlüter, Achim; Vance, Colin; Ferse, Sebastian
Abstract: Coral reefs are subject to multiple stressors. Global stressors include climate change and ocean acidification, while local stressors include overfishing and eutrophication. Some stressors stem from land-based activities, like intensive agriculture or sewage production, while others are sea-based, like fishing or diving. Processes that aim to tackle coral degradation are transpiring on different levels. These include the UNDP's Sustainable Development Goal 14, and the Coral Triangle Initiative, which foresees the installation of marine protected areas and conservation planning. This paper uses Evolutionary Governance Theory (EGT) to understand the current processes of changes in governance influencing coral reef health. EGT sees the change of governance as an evolutionary process. It emphasises that discourses play a crucial role in understanding governance evolution. Power, in particular power-knowledge in the Foucaultian sense, plays a crucial role as a driving factor. Governance does not change in a vacuum, but according to EGT is shaped by path, inter- and goal dependencies. Of late, the role of materiality - ecological and technological conditions - has been stressed as an important driver of governance change. The paper considers the main threats to corals identified in the literature and analyses how those factors mentioned by EGT help us to understand the observed governance changes. The case of coral reefs was chosen as it represents an example of extremely diverse processes of institutional changes. Therefore, it is well suited to learn if EGT helps in understanding governance changes observed in the marine sector.